Entrepreneurial intention among undergraduates from B40 group : A case study in UiTM Kelantan Campus / Siti Rosnita Sakarji ... [et al.] - Sakarji, Siti Rosnita; Shari, Asma Shazwani; Mohd Ishak @ Zainudin, Fadhilah; Mohd Hatta, Siti Anisah (2021)
Various higher learning institutions in Malaysia offers Entrepreneurship courses to nurture interest among students in becoming entrepreneurs. Furthermore, the revolution of Information and Communications Technology (ICT) resulted in an emerging digital economy in all countries including Malaysia. The promising phenomenon gradually emerges as a significant essence in developing entrepreneurship as a career choice among the young generation, particularly students with entrepreneurial background courses enrolment at university level. However, the entrepreneurial participation rate among graduates is still low. This conceptual paper aims to examine the intention and factors that determine digital entrepreneurial intention among undergraduates from the B40 group at Universiti Teknologi MARA Machang Campus, Kelantan (UiTMCK). The respondents are selected from the B40 group enrolled in courses like ENT300, ENT530 and ENT600 from multiple programs. This study employs the Theory of Planned Behaviour (TPB) as a theoretical framework. The independent variables of this study consist of personal attitudes, subjective norms and perceived behavioural control. This paper examines the intention and motivation of entrepreneurship students that may contribute to their decision to become entrepreneurs. The main limitation of this study is it only involves one public higher learning institution, therefore the results might be "institution-specific". The researcher increases number of samples, utilizes various samples from multiple entrepreneurial institutions and conducts a comparative study in order to create more comprehensive and insightful outcome